Dampak Covid-19 : Stres pada Orang Tua dengan Kejadian Emotional Abuse pada Pembelajaran Jarak Jauh (PJJ) - Fitria, Dian; Silalahi, Malianti; Setyaningsih, Tri; Yesayas, Fendy (Jurnal Kesehatan Holistic, 2022)
Introduction: the Covid-19 has made all aspects of life adapt to a new pattern of life. Learning method has changed to be a online distance learning. The role of parents in this methods, have agreat enough proportion for assistance, especially for elementary school-aged children. This is a additional tasks for parents, and can generate a new burden and daily stress. The patience of parents in providing assistance is needed, because it will cause violence to children, such as verbal and behavioral violence, which causes children to experience emotional abused. Objective: this research was conducted to find out how the behavior of students during the adaptation period of new habits, the influence of knowledge on Covid-19 prevention behavior and the factors that influence student behavior in preventing Covid-19. Methods: this research is a quantitative research with a cross sectional design. Data analysis using Pearson correlation test. The research sample was 285 parents assistance online learning for elementary school-aged children, with non-probability sampling method. Result: results showed that there was a significant and positive relationship correlation between stress on online learning assistance and emotional abused conducted on children, (P = 0.0005). Conclusion: parents need education about the impact of emotional abused on their children and Educational institutions need to pay attention to the level of comprehension of parents in assistance children's learning, especially in the use of systems or applications learning.